A long-term evaluation of arthroscopy of the temporomandibular joint using holmium YAG laser - Renato Mazzonetto; Sandra de Cássia Santana Sardinha; Daniel B. Spagnoli (Universidade Estadual de Campinas, 2015)
The aim of this in vivo study was report the long-term results of arthroscopic laser surgery for treatment of TMJ internal drangements (Wilkes class II-III). This report included 45 patients (42 women and 03 men) with an average age of 36.7 years old (14 to 66 years). There were 69 joints involved. The criteria for inclusion were patients who had complained of TMJ pain and dysfunction and had remained refractory to nonsurgical treatment for at least 3 months without resolution of the problem. All patients filled out a questionnaire preoperatively and postoperativelly for assessment of their signs and symptoms. The range of interincisal opening was measured preoperatively and at 1, 7, 30, and 60 days after the surgery. The postoperative questionnaire, radiographic evaluation, and the last measure of range of motion were performed with one year or more after the surgical procedures. The preoperatively and postoperativelly scores were compared and tested for statistically significant differences by the paired t-test (P>0.05). Forty-five patients (69 joints) have been followed postoperativelly for an average of 28.6 months. Maximal interincisal opening improved from a mean of 25.95mm to 35.91mm (+9.96mm) in seven days after the surgery; to 39.86mm (+3.95mm) after thirty day and; to 40.92mm (+1.06mm) after 60 days. The last measurement of maximal interincisal opening made after one year or more showed a mean of 42.15mm. All postoperative VAS pain scores showed a statistical significant improvement (p<0.05). The overall success rate for arthroscopy arthroplasty with Holmium YAG laser was 93.3% (42 of 45 patients) in a mean follow-up of 28.6 months. No complications were observed. Based on the results we can conclude that arthroscopic arthroplasty with Holmium laser is a safe and effective tool for the treatment of TMJ internal derangements.